2009
DOI: 10.2174/092986709788803240
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Receptor Protein Tyrosine Phosphatase β /ζ: A Potential Therapeutic Strategy for Parkinsons Disease

Abstract: striatum of rodents in experimental models of Parkinson's disease. Interestingly, immunohistochemical studies have shown increased levels of PTN expression in the substantia nigra of patients with Parkinson's disease. Since, in other contexts, PTN has been shown to be critical in repair processes in the injured nervous system, the antecedents suggest that PTN could exhibit protective effects in Parkinson's disease. This hypothesis was confirmed when PTN was shown to support survival of dopaminergic neurons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 89 publications
0
37
0
Order By: Relevance
“…The present study did not examine the mechanism by which PTN elicits neuroprotection, but experiments in which RPTP / function is blocked suggest that PTN-RPTP / interactions may be key to generating neuroprotective effects (for review, see ref. 35). Inhibition of protein tyrosine phosphatases in the SN preserves striatal dopaminergic projections and SN dopaminergic neurons following nigral 6-OHDA lesioning.…”
Section: Discussionmentioning
confidence: 99%
“…The present study did not examine the mechanism by which PTN elicits neuroprotection, but experiments in which RPTP / function is blocked suggest that PTN-RPTP / interactions may be key to generating neuroprotective effects (for review, see ref. 35). Inhibition of protein tyrosine phosphatases in the SN preserves striatal dopaminergic projections and SN dopaminergic neurons following nigral 6-OHDA lesioning.…”
Section: Discussionmentioning
confidence: 99%
“…The PTN and MK genes are widely expressed at different times in different cell types during development (Silos‐Santiago et al ., ; Deuel et al ., ; Muramatsu, ). However, the expression of both PTN and MK genes is constitutive and limited to only a few cell types in adults (Herradon and Ezquerra, ; Muramatsu, ). Both genes are up‐regulated at sites of injury and repair in inflammatory macrophages, microglia, dermal fibroblasts, endothelial cells and other cells (Jin et al ., ; Martin et al ., ; Muramatsu, ), suggesting PTN and MK signalling may be critical in different steps of differentiation of different cells both in development and in wound repair.…”
Section: Mk and Ptn: Cytokines With Important Roles In Neural Repair mentioning
confidence: 99%
“…For this reason, PTPs (including the receptor‐like class) are currently being considered as prime targets for drug design (Wong et al ., ) following the path opened by selective PTK inhibitors that were previously developed and reached clinical use (Ventura and Nebreda, ). Pharmaceutical development of therapeutics targeting PTPs has been proposed to treat a wide variety of diseases including diabetes mellitus, neural diseases such as PD and Alzheimer's disease, inflammatory diseases and allergy (Herradon and Ezquerra, ; Heneberg, ).…”
Section: Activation Of Mk/ptn Signalling Pathways: a Novel Therapeutimentioning
confidence: 99%
“…In addition, the expression of PTN is elevated in a number of cancer cell lines, and the expression level often correlates with the metastatic abilities of these cancer cells [5][6][7][8][9][10][11][12][13]. However, PTN expression can also be beneficial: studies have shown that PTN helps to maintain hematopoietic stem cells, triggers tissue repair during ischemia and provides protective effects on neural tissues during addiction [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%